If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3y + -7) = 34 Reorder the terms: 2(-7 + 3y) = 34 (-7 * 2 + 3y * 2) = 34 (-14 + 6y) = 34 Solving -14 + 6y = 34 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 6y = 34 + 14 Combine like terms: -14 + 14 = 0 0 + 6y = 34 + 14 6y = 34 + 14 Combine like terms: 34 + 14 = 48 6y = 48 Divide each side by '6'. y = 8 Simplifying y = 8
| 3x+3x+6=18 | | 5*1.2=n | | i^41= | | 118-2x=x^2-18x+82 | | 7x=8(5x+6) | | -9r^2-5=605 | | 8x-(5x-6)=27 | | 3y+7=2(y-3) | | (39x-27)-(25x-48)=(34x-17)-(23x-63) | | x+(x*0.12)=35 | | 4y-5+y+49=7y+50-5y | | 3a-5=-8(6+5a) | | 2x+11x=-39 | | 8=9tanx | | 3x-15=85 | | 2xy+6y= | | -3y+6-2y+4=20 | | 14=x-65 | | 11(z+1)-3(z-2)=4(z-1)+3(z-2) | | -222=8(5n-7)-6 | | 5x+2(7x+17)=148 | | .25y-3.5=.15y+1-.8y | | [2k+6]=[k] | | 9b^2+18b=-8 | | -14=5y+6 | | 4s-28=-14+2s | | 7(x+6)9=9 | | 3x-4-4x=5-5x+3x | | -39=-5v+3(v-7) | | -5(x+6)9=9 | | [2r+5]=3r | | -3(x+6)3=9 |